Penerapan Algoritma Genetika untuk Menghitung Biaya Optimal Komposisi Bahan Makanan pada Penderita Uric Acid - Kurniasari, F; Andayani, P (Jurnal Teknologi dan Informasi (JATI), 2021)
An unbalanced diet with a very high protein intake causes high levels of uric acid in the body. Uric Acid is a disease caused by high levels of uric acid in the human body. In Indonesia, Uric Acid is one type of disease that many Indonesians suffer from. Angriani's research (2018) states that the highest cause of uric acid is due to too high purine intake. For several people, managing their daily diet has become a difficult task. To overcome this problem, in this study, a system of selecting food ingredients for uric acid sufferers was developed using a genetic algorithm. In this study, 50 food ingredients were used with their respective nutritional content (carbohydrates, protein, fat). The chromosome representation used is a permutation of an integer number that has a chromosome length of 15. The results obtained from this study are food recommendations for people with uric acid (uric acid) with details on the name of food ingredients, weight, calorie content, carbohydrate content, protein content, content. fat, and the price. The total cost price is also displayed, to predict the costs incurred.